The identity of the individual in the Psalms - Croft, Steven J. L. (Journal for the study of the Old Testament. Supplement series, 1987)
The first monograph devoted to this perennial question in Psalm study for three-quarters of a century, Croft's work provides a fresh and comprehensive treatment. The initial chapters approach the central issue via the associated problems of the identity of the psalmists' enemies and the psalmists' description of themselves as 'poor'. In the remaining three chapters all the psalms in which an 'I' speaks are examined under one of three headings: royal psalms, psalms intended for use by a private person and those to be delivered by a minister in the cult, a prophet, wisdom teacher or temple singe.